2001
DOI: 10.1016/s0304-3959(01)00271-8
|View full text |Cite
|
Sign up to set email alerts
|

Central activation by histamine-induced itch: analogies to pain processing: a correlational analysis of O-15 H2O positron emission tomography studies

Abstract: The aim of this study was to identify the functional cerebral network involved in the central processing of itch and to detect analogies and differences to previously identified cerebral activation patterns triggered by painful noxious stimuli. Repeated positron emission tomography regional cerebral blood flow (rCBF) measurements using O15-labeled water were performed in six healthy right-handed male subjects (mean age 32 +/- 2 years). Each subject underwent 12 sequential rCBF measurements. In all subjects a s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

14
164
2
7

Year Published

2003
2003
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 234 publications
(187 citation statements)
references
References 47 publications
14
164
2
7
Order By: Relevance
“…34 The multidimensionality of itch is indicated as multiple areas of the brain are activated when itch is induced. Drzezga et al 35 used PET scanning to study the central processing of histamine-induced itch. They noted significant activation of contralateral somatosensory cortex, as well as contralateral and ipsilateral motor areas, but no thalamic activation.…”
Section: 1322mentioning
confidence: 99%
“…34 The multidimensionality of itch is indicated as multiple areas of the brain are activated when itch is induced. Drzezga et al 35 used PET scanning to study the central processing of histamine-induced itch. They noted significant activation of contralateral somatosensory cortex, as well as contralateral and ipsilateral motor areas, but no thalamic activation.…”
Section: 1322mentioning
confidence: 99%
“…Beyond these regions, alterations in neuronal activities in several brain areas were reported in relation to itch processing above the thalamus; these include the primary and secondary somatosensory cortex, the premotor and supplementary motor cortex, the inferior parietal lobe, the cerebellum as well as certain temporal regions [34][35][36][37][38][39][40]. Although there are slight variations in the itch-related regions reported among studies, which could be due to different experimental designs [40], there is a consensus in the literature about the following: (i) the sensory-discriminative component of itch is likely processed in the primary somatosensory cortex; (ii) the activities of the anterior cingulate and insular cortex may be related to the motivational and affective components; (iii) the motor component of the goal-directed scratching is attributed to the premotor and supplementary motor areas; (iv) these brain regions are also involved in the central pain processing; therefore, distinction of the two sensations is mainly based on the differential activation patterns of mostly identical centers [4, 10, 35-37, 41, 42].…”
Section: Higher Itch Centersmentioning
confidence: 99%
“…Several studies have revealed that brain processing of itchy stimuli in patients with chronic pruritus differs from that observed in healthy controls [34][35][36]. Thus, it could be suggested that mapping of brain activity during itch episodes may provide valuable information helping in the assessment of the degree of itch intensity.…”
Section: Assessment Of Brain Activitymentioning
confidence: 99%
“…However, current data are rather preliminary, as there is great variability in currently achieved results with different diagnostic techniques. These methods are also too expensive to be used as a routine diagnostic procedure, and thus they are used only for scientific purposes to better understand what happens within the brain upon itchy stimuli [34][35][36].…”
Section: Assessment Of Brain Activitymentioning
confidence: 99%